Heroes or criminals: discursive representation of cancer patients in health awareness advertisements. (May 2021) - Ho, Janet
This article compares the use of metaphors in breast and lung cancer awareness advertisements in order to examine the positioning and identity construction of the respective cancer patients. A semantic annotation software tool was used to identify the overuse of semantic fields in each corpus of cancer awareness advertisements and multimodal metaphors were identified following the protocols of Bounegru and Forceville's (2011) article, 'Metaphors in editorial cartoons representing global financial crisis', Forceville's (2009) essay, 'Non-verbal and multimodal metaphor in a cognitivist framework: Agendas for research' and Pérez-Sobrino's (2017) book, Multimodal Metaphor and Metonymy in Advertising . Findings showed that breast cancer awareness advertisements deployed more positive words than did the lung cancer awareness advertisements and they used a wide range of source domains such as WILD ANIMALS and FIGHTERS, showing the creative representation of deeply entrenched conventional metaphors as well as the use of humour and euphemism. On the other hand, lung cancer awareness advertisements were much less metaphorical and mostly sought to persuade people to quit smoking. The metaphorical use of military weapons showed that 'shockvertising' was recurrent in lung cancer awareness advertisements. The present study argues that both types of advertisements partially present the facts of breast cancer and lung cancer, and the guilt-loading of smokers in the lung cancer awareness advertisements invisibly transformed the physical threat appeals into social threat appeals.